The Use of Aqueous Extract of Myrtle Plant Leaves in the Treatment of Chronic Bacterial Vaginosis - Essa, Prof. Dr. Muhsin A.; Najm, Dr. Yusra Y.; Mohamed, Abdullah I. (American Journal of Biomedicine and Pharmacy, 2025)
The current study aimed to evaluate the activity of the aqueous extract of the Myrtle plant (Myrtus communis) in treating patients with chronic bacterial vaginosis. Additionally, its inhibitory effect on aerobic bacteria and Candida isolated from vaginosis infections was studied, and antibiotic susceptibility of the isolates was also assessed. The results of the diagnoses through aerobic incubation showed that Staphylococcus aureus, Staphylococcus haemolyticus, Escherichia coli, and Candida albicans were the most commonly isolated organisms from the studied vaginosis infections. Antibiotic sensitivity results indicated that all the isolates exhibited patterns of multiple antibiotic resistance. The findings suggest that the aqueous extract of myrtle leaves demonstrated a clear inhibitory effect against all studied microbes at all concentrations, with the effect increasing as the concentration increased. The highest inhibition was observed at a 20% (w/v) concentration, with inhibition zones of 32 mm for S. haemolyticus, 30 mm for S. aureus, 27 mm for E. coli, and 38 mm for C. albicans. The study included the use of a 20% aqueous extract of myrtle leaves for the treatment of 20 patients with chronic vaginosis, resulting in improvements in most patients starting from the third day of treatment. Various symptoms continued to disappear thereafter, and all patients achieved complete recovery by the end of the treatment week. This reflects the ability of the extract to alleviate all symptoms associated with the studied vaginosis infections, suggesting its potential as a safe and effective alternative treatment for these infections.